The perception of discretionary accounting regulations on asset write-offs - Maruszewska, Ewa Wanda (Postrzeganie elastycznych regulacji rachunkowości w zakresie odpisów aktualizujących aktywa, 2019)
Flexibility of accounting norms (in the scope of asset write-offs) was introduced in order to enable entities to apply solutions adjusted to their specific character, creating+ – * the possibility to use discrete decision-making in a way that undermines the theoretical foundations of accounting. The disfunction lowers the faithful representation of financial reports. The aim of this study is to analyse the perception of discrete accounting in the context of financial reporting. The study was conducted among part-time accounting students with the high level of previous accounting experience. The findings showed that the respondents were not eager to use write-offs for manipulation purposes but were strongly convinced that other accountants would behave unethically. They also suggested that faithful representation is not perceived as a social norm among accounting professionals and that the perception of asset write-offs differs depending on the group of assets. In the conclusion, the study indicated a gap between the theoretical foundations of accounting and their application in business practice
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 77-87